CowLog – Cross-Platform Application for Coding Behaviours from Video. Issue 1 (27th April 2016) - Pastell, Matti
CowLog is a cross-platform application to code behaviours from video recordings for use in behavioural research. The software has been used in several studies e.g. to study sleep in dairy calves, emotions in goats and the mind wandering related to computer use during lectures. CowLog 3 is implemented using JavaScript and HTML using the Electron framework. The framework allows the development of packaged cross-platform applications using features from web browser (Chromium) as well as server side JavaScript from Node.js. The program supports using multiple videos simultaneously and HTML5 and VLC video players. CowLog can be used for any project that requires coding the time of events from digital video. It is released under GNU GPL v2 making it possible for users to modify the application for their own needs. The software is available through its websitehttp://cowlog.org .